Risk Factor of Preeclampsia in Najaf Governorate - Majid khadum Hussein; Dhaferah Jaafar Abd Ali; Zahraa Sami Razzaq (Kufa Journal for Nursing Sciences)
Objective: It aim to study some of the risk factors and a association Preeclampsia